2017
DOI: 10.1136/bmjopen-2016-014710
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of non-communicable disease risk factors among poor shantytown residents in Dhaka, Bangladesh: a community-based cross-sectional survey

Abstract: ObjectivesThis study aims to describe the prevalence of non-communicable disease (NCD) risk factors among the urban poor in Bangladesh.DesignWe conducted a community-based cross-sectional epidemiological study.SettingThe study was conducted in a shantytown in the city of Dhaka. There were 8604 households with 34 170 residents in the community. Those households were categorised into two wealth strata based on the housing structure.ParticipantsThe study targeted residents aged 18–64 years. A total of 2986 eligib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
52
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 29 publications
3
52
3
Order By: Relevance
“…11 The recent Global Adult Tobacco Survey reported almost constant finding for tobacco use with our study whereas data from WHO STEPS Survey and another study conducted to identify NCD risk factors among an underprivileged population in Dhaka reported noticeably higher prevalence of tobacco users. [14][15][16] Moreover, another relevant study conducted among rural population of Bihar state of India using similar WHO Step wise approach reported higher prevalence of tobacco use than the current study. 17 The possible reason of less prevalence of tobacco use in this study could be due to the under reporting about tobacco uses by the respondents.…”
Section: Discussionmentioning
confidence: 47%
See 3 more Smart Citations
“…11 The recent Global Adult Tobacco Survey reported almost constant finding for tobacco use with our study whereas data from WHO STEPS Survey and another study conducted to identify NCD risk factors among an underprivileged population in Dhaka reported noticeably higher prevalence of tobacco users. [14][15][16] Moreover, another relevant study conducted among rural population of Bihar state of India using similar WHO Step wise approach reported higher prevalence of tobacco use than the current study. 17 The possible reason of less prevalence of tobacco use in this study could be due to the under reporting about tobacco uses by the respondents.…”
Section: Discussionmentioning
confidence: 47%
“…Although insufficient fruit and vegetables intake behaviour is remarkably higher in previous studies in Bangladesh, however, it was found extremely higher in our study even compared to Indian Bihari population also. [15][16][17] Added salt intake behaviour in meal among the current study population wasn't noticeably varied than the Bangladeshi general population as well as the underprivileged population. 16,[18][19][20] Inadequate level of PA was noticeably higher among the selected population in contrast to the general population of this country reported in national survey report and underprivileged population of Bangladesh, and also the Indian Bihari population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The impact of NCDs on the national economy, communities, families and individuals is unbearable [10,16,17], and this is likely to be more serious in coming years [18][19][20]. Recent studies have shown that NCD risk factors such as overweight, underweight, hypertension, dyslipidemia, physical inactivity, tobacco smoking and low consumption of vegetables were common among adults living in urban [21][22][23] as well as rural areas [22,24] including adults of all economic quintiles [10].…”
mentioning
confidence: 99%